Mechanical performance of carbon-epoxy laminates. Part I: quasi-static and impact bending properties - Tarpani,José Ricardo (2006)
In Part I of this study, quasi-static and impact bending properties of four aeronautical grade carbon-epoxy laminates have been determined and compared. Materials tested were unidirectional cross-ply (tape) and bidirectional woven textile (fabric) carbon fiber lay-up architectures, impregnated with standard and rubber-toughened resins, respectively, giving rise to 1.5 mm-thick laminates. Quasi-static mechanical properties assessed in transversal mode loading were modulus of elasticity, flexural strength and tenacity at the maximum load, whereas the net absorbed energy was determined under translaminar impact conditions. Two-dimensional woven carbon fiber reinforcements embedded in a rubber-toughened matrix presented the best mechanical performance under static loading. Under dynamic loading conditions, woven fiber fabric pre-forms were favorably sensitive to increasing impact energies regardless the nature of the employed epoxy resin. However, it was concluded that great care should be taken with this material within the low energy impact regimen.